2017
DOI: 10.1002/2016jd025834
|View full text |Cite
|
Sign up to set email alerts
|

Frequency spectra and vertical profiles of wind fluctuations in the summer Antarctic mesosphere revealed by MST radar observations

Abstract: Continuous observations of polar mesosphere summer echoes at heights from 81–93 km were performed using the first Mesosphere‐Stratosphere‐Troposphere/Incoherent Scatter radar in the Antarctic over the three summer periods of 2013/2014, 2014/2015, and 2015/2016. Power spectra of horizontal and vertical wind fluctuations, and momentum flux spectra in a wide‐frequency range from (8 min)−1 to (20 days) −1 were first estimated for the Antarctic summer mesosphere. The horizontal (vertical) wind power spectra obey a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
41
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 61 publications
8
41
1
Order By: Relevance
“…1b to better understand their height distributions. Summer echoes in December, January, and February are mostly confined to altitudes of 80−90 km and are rarely seen outside this region, which is a well-known feature of PMSEs (e.g., Sato et al 2014Sato et al , 2017. Non-summer echoes between mid-March and mid-November are seen mostly at altitudes of 55−80 km, which is in line with the reported features of PMWEs over Syowa (Nishiyama et al 2015).…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…1b to better understand their height distributions. Summer echoes in December, January, and February are mostly confined to altitudes of 80−90 km and are rarely seen outside this region, which is a well-known feature of PMSEs (e.g., Sato et al 2014Sato et al , 2017. Non-summer echoes between mid-March and mid-November are seen mostly at altitudes of 55−80 km, which is in line with the reported features of PMWEs over Syowa (Nishiyama et al 2015).…”
Section: Resultssupporting
confidence: 75%
“…PANSY echoes reproduced reported results by Sato et al (2014Sato et al ( , 2017 and Nishiyama et al (2015): summer echoes (PMSEs) were mostly confined to the height region of 80−90 km, and winter echoes (PMWEs) were mostly below 80 km during the daytime and for a few extended hours after sunset. This somewhat asymmetric structure about the local noon in winter was also depicted in the MAARSY observations in the Arctic (Latteck and Strelnikova 2015) although not explicitly mentioned.…”
Section: Discussionsupporting
confidence: 70%
“…The momentum flux frequency spectra ( ω Re [ U ( ω , z ) W * ( ω , z )] and ω Re [ V ( ω , z ) W * ( ω , z )]) are also estimated (see Sato et al, , for details of this method) and are shown in their flux‐content form in Figure as a function of frequency and height. In the troposphere, ω Re [ U ( ω , z ) W * ( ω , z )] and ω Re [ V ( ω , z ) W * ( ω , z )] are negative for ω < 2 π /12 hr.…”
Section: Statistical Analysis Methodsmentioning
confidence: 99%
“…From trueG¯false(τ,0false) and G 4 h′ ( τ ,0), it is possible to see a strong peak around 3‐hr wave periods—this is consistent with the mean wind residuals shown in Figure and the oscillations that can be seen in the corresponding autocorrelation function. Sato et al () also report the presence of a 3‐hr wave. Our spectra only contains 1 day of measurements, so the fidelity is not as good.…”
Section: Resultsmentioning
confidence: 93%